2022
DOI: 10.1097/qai.0000000000002945
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing at Visits to US Emergency Departments, 2018

Abstract: Background: An early HIV diagnosis improves patient outcomes, reduces the burden of undiagnosed HIV, and limits transmission. There is a need for an updated assessment of HIV testing rates in the emergency department (ED). Setting:The National Hospital Ambulatory Medical Care Survey sampling ED visits were weighted to give an estimate of ED visits across all US states in 2018. Methods:We analyzed patients aged 13-64 years without known HIV and estimated ED visits with HIV testing and then stratified by race, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…We also identified persistently low rates of HIV testing for populations prioritized in the EHE phase 1 rural jurisdictions in the South. This is consistent with previous estimates showing that both populations and regions disproportionately affected by HIV had low HIV testing rates [3]. Despite 7.7 million fewer weighted emergency department visits during the COVID-19 pandemic in 2020 than 2019, we found that testing rates were stable between 2019 and 2020.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We also identified persistently low rates of HIV testing for populations prioritized in the EHE phase 1 rural jurisdictions in the South. This is consistent with previous estimates showing that both populations and regions disproportionately affected by HIV had low HIV testing rates [3]. Despite 7.7 million fewer weighted emergency department visits during the COVID-19 pandemic in 2020 than 2019, we found that testing rates were stable between 2019 and 2020.…”
Section: Discussionsupporting
confidence: 92%
“…System-level interventions, such as access to rapid testing platforms, standing orders for opt-out testing, or clinical decision support tools programmed in the electronic health record system, can increase HIV testing rates in the emergency department setting. Interventions like this have a high diagnostic yield because of the HIV rates of HIV diagnoses in communities served in the emergency department, including persons who inject drugs presenting after an overdose; those with STIs; and those who are underinsured or uninsured without alternative means of testing [3,4]. However, the lack of an increase in rates of Copyright © 2023 Wolters Kluwer Health, Inc. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations